Tingkat Pengetahuan Masyarakat Desa Tanete Kabupaten Sidrap tentang Penggunaan Desinfektan untuk Pencegahan Virus Corona - Reny Anggreani Hakim; Nurlela (Universitas STRADA Indonesia, 2020)
The level of knowledge of the people of the Tanete Village in Sidrap Regency about the use of disinfectants for the prevention of the corona virus. This type ofresearch is a quantitative study.This research is carried out with a collection of objects which aims to determine the level of knowledge of the community in the village of Tanete, Sidrap Regency about the use of disinfectants for the prevention of the corona virus. The level of knowledge based on tofu contained 50 people who answered YES with a percentage (94.3%) while the respondents who answered NO were 3 people with a percentage (5.7%). The level of knowledge based on understanding there were 53 people who answered YES with a percentage (100%) while the respondents who answered NO were 0 people with a percentage (0%). The level of knowledge based on the application, there were 38 people who answered YES with a percentage (71.7%) while the respondents who answered NO were 15 people with a percentage (28.3%). The level of knowledge based on the analysis contained 51 people who answered YES with a percentage (96.2%) while the respondents who answered NO were 2 people with a percentage (3.8%). The level of knowledge based on synthesis, there were 39 people who answered YES with a percentage (73.6%) while 14 people answered YES with a percentage (26.4%). The level of knowledge based on the evaluation contained 40 people who answered YES with a percentage (75.5%) while the respondents who answered NO were 13 people with a percentage (24.5%).